Identification of the macromolecular complex responsible for PI3Kγ-dependent regulation of cAMP levels. (21st July 2006) - Perino, A.; Ghigo, A.; Damilano, F.; Hirsch, E.
Abstract : PI3Kγ is a phosphoinositide 3-kinase characterized by both lipid and protein kinase activity. It is activated by G-protein-coupled receptors and is predominantly expressed in leucocytes; in addition, recent work showed its presence in the heart and its involvement in regulating cardiac functions. In this tissue, PI3Kγ acts as a negative modulator of contractility, by decreasing cAMP concentration through a kinase-independent mechanism. Indeed, whereas PI3Kγ-deficient mice show an abnormal cAMP elevation, cAMP levels in knock-in mouse mutants, expressing a kinase-dead PI3Kγ, are comparable with wild-type controls. PI3Kγ regulates cardiac cAMP homoeostasis by forming a macromolecular complex containing PDE3B (phosphodiesterase 3B). In this complex, PI3Kγ could regulate PDE3B activity through protein kinase A, a PDE activator.